Investigating Everyday Prospective Memory in Younger and Older Couples. (17th December 2021) - Haas, Maximilian; Meier, Tabea; Huber, Zilla; Kliegel, Matthias; Horn, Andrea
Abstract: Daily events are not simply individual concepts, but shared by the social environment we live in. The present study investigates the role of romantic partners in the co-regulation of cognitive functioning by the example of prospective memory (PM), the ability to remember and correctly execute future intentions. In this context, we examined the impact of social proximity (i.e., physical closeness and psychological intimacy) on interpersonal regulation. Over the course of 21 days, 64 younger couples (18-33 years) and 52 couples of older adults (57-87 years) completed an ambulatory assessment comprising a daily pseudo-randomized PM task. Results reveal that couples' PM performance was higher for younger than for older participants. Further, dyadic PM was correlated with psychological intimacy for both age groups, but the impact of time spent together on intimacy and PM performance, respectively, was stronger in older adults. Possible moderating factors and explanations for these findings will be discussed.